2018
DOI: 10.18203/2349-2902.isj20181599
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of Alpha blocker (Silodosin) and Phosphodiesterase type 5 inhibitor (Tadalafil) in benign prostate hyperplasia patients with lower urinary tract symptoms: a single centre study

Abstract: Background: Benign prostatic hyperplasia (BPH) is a histologic diagnosis that refers to the proliferation of smooth muscle and epithelial cells within the prostatic transition zone. The aim of this systematic review is to determine the comparative effectiveness and safety of phosphodiesterase 5 inhibitors (PDE5-Is) and alpha blockers used alone or in combination for the treatment of lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH).Methods: We analyzed 54 patients of BPH with LUTS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Furthermore, our findings were consistent with those of Oelke et al (2012) on 511 patients with LUTS/BPH who showed that Qmax rose considerably with Tadalafil versus placebo, with a mean difference of 2.4± 5.5 ml/sec vs. 1.2 ±4.8 ml/sec) [11]. This is also supported by the study conducted by Singh et al (2018) on patients with LUTS or BPH, who reported that Qmax increased significantly with Tadalafil from 13.36 to 15.00 ml/sec after four weeks and further to 17.38 ml/sec after 12 weeks [12].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our findings were consistent with those of Oelke et al (2012) on 511 patients with LUTS/BPH who showed that Qmax rose considerably with Tadalafil versus placebo, with a mean difference of 2.4± 5.5 ml/sec vs. 1.2 ±4.8 ml/sec) [11]. This is also supported by the study conducted by Singh et al (2018) on patients with LUTS or BPH, who reported that Qmax increased significantly with Tadalafil from 13.36 to 15.00 ml/sec after four weeks and further to 17.38 ml/sec after 12 weeks [12].…”
Section: Discussionsupporting
confidence: 91%